Understanding the Livelihood Characteristics of the Migratory and Non-Migratory Fishers of the Padma River, Bangladesh - Khan, M. I.; Islam, M. M.; Kundu, G. K.; Akter, M. S. (Journal of Scientific Research, 2018)
The Padma is the second longest and one of the trans-boundary rivers of Bangladesh that significantly contributes to fisheries production and supports the fishers’ livelihoods. This study assesses the livelihood characteristics of the Padma river-dependent migratory and non-migratory fishers, employing household interviews, focus group discussions (FGDs), and key informant interviews from July to October, 2015. All migratory fishers were full-time fishers, whereas, non-migratory fishers included full time (88.89%), part-time and occasional fishers (11.11%). Maximum fishers were belonging to the age group of 31 to 50 years of which 94.74% were migratory and 57.4% were non-migratory fishers. Half of the migratory and non-migratory fishers were illiterate. 89.47% migratory fishers used river water for drinking and other purposes, whereas, 94.44% non-migratory fishers used tube-well water. Average annual incomes of both migratory (58%) and non-migratory (65%) fishers ranged from Tk. 30,000 to 60,000, whereas 26% migratory and 5% non-migratory fishers had average annual incomes above Tk. 60,000. The overall livelihood status of the migratory and non-migratory fishers was not satisfactory as they have faced problems like conflicts with elite groups for resources, lack of fish preservation facilities. Effective initiatives and their proper implementations are very crucial to develop the Padma river fisher’s livelihood conditions.